Proyecto de factibilidad para la implementación de una empresa productora y comercializadora de confitería en base a maní para la provincia de Loja, con materia prima de los productores de los cantones Paltas y Celica beneficiarios del grupo social FEPP. - García Alba, Carmen Julia (2012)
The thesis project has as purpose to determine the planeación and short term results of the execution of a company Producer and Comercializadora of Confitera in the County of Loja, to give to know the importance and necessity of executing it. This is not due to the existence of companies producers and sweet shop comercializadoras based on peanut in the county of Loja and for the lack of knowledge in managerial formation. In our Country and county we have the Ecuadorian Fund Populorum Progressio (FEPP) that is devoted to carry out support economic technician mainly to women, men and peasants to the South Region of Ecuador in the cantons of Avocados and Celica in the realization of projects of community development implementing education, access possibility to work sources and production means, transformation and commercialization. It is hence that this project goes guided to the use of the matter it prevails like it is the peanut the same one that exists in the cantons of Avocados and Celica, and that they are beneficiaries of the social Group FEPP. To determine the feasibility to implement a company producer and sweet shop comercializadora based on peanut taking advantage of the matter it prevails this way existent in the cantons of Avocados and Celica the cultivation of the peanut is since very important in the economy of many families of the rural sector being one of the products of high production level. It is hence that our study of feasibility for the implementation, commercialization and peanut production with sweet in the County of Loja, shows different aspects of the current situation of the peanut it stops this way to determine the viability of the same one. The methodology that was applied for the realization of our investigation was the method (deductive, synthetic) and through a survey applied the population of the county of Loja, and at the same time allowing us to obtain data the same ones that were analyzed and evaluated and this way to present alternative possible 5 for the development of the investigation. The project is deepened basically in three important aspects as they are: I study market, technical study, financial study. The market study which was carried out to 399 families of the County of Loja distributed porcentualmente, what allowed to determine that in our county an appreciable peanut demand exists with 83% and of peanut with sweet with 33% of the total of this demand, reflecting an unsatisfied demand of the so much product for direct consumption, like for the industrialization in its different forms. In the Technical study he/she shows up information selected on the processes of production technological aspects and their organizational structure all this necessary to reach a production of quality that you/they reflect an investment in active fixed of 62.944,21 that added to the differed assets and circulating they represent an initial investment of $ 72.865,67, to be financed 70% by the shareholders and 30% bank credit; they have also been carried out the calculation of the indicators of profitability and feasibility of the project like they are: Current Net value that was determined in 50.130,66; also the Internal Rate of Return that is of 36,21%; likewise the Analysis of Sensibility indicates that the project supports until 9,90 increment% in the costs and 7,05% decrees in the revenues; the Relationship was also calculated I Benefit Cost that is $1,38, what indicates that for each invested unit it is obtained 0,38 of utility; finally the Period of Recovery of the Capital that will be given in 3 years 10 months, settled down if the conditions occur he/she conforms to it outlines the project. Everything allows us to it to conclude that a feasibility of the project, reason for the one exists which shows up like a good production alternative in benefit of the county of Loja and the producing beneficiaries of the social Group FEPP of the Cantons of Avocados and Celica; allowing to our county to improve its economic structure and work sources are believed since instead of selling the products in matter quality it prevails for the industrial sector, you offers the opportunity to process it in the cultivation area, and this way to energize the local economy.